The effect of customized woven and stacked layer orientation on tensile and flexural properties of woven kenaf fibre reinforced epoxy composites - Hamdan, A.; Mustapha, F.; Ahmad, K. A.; Mohd Rafie, A. S.; Ishak, M. R.; Ismail, A. E. (Hindawi Publishing Corporation, 2016)
The synthetic fibres have created some issues including risk of inhalation during fabrication process, renewability, biodegradability, and recyclability in composites industry. The usage of biocomposites as a replacement to synthetic fibres is beginning to be widespread. However, it is noted that lesser attention has been devoted to evaluating the mechanical properties of woven kenaf composites at various woven and stacked layer orientation. Thus, the research objective is to identify the effect of woven and stacked layer orientation on tensile and flexural properties of kenaf composites. Two types of fibre orientation are employed; type A contains a higher yarn density and type B contains a low yarn density. The tensile and flexural tests are conducted to analyze the mechanical properties of woven kenaf fibre composites and compare them to random chopped kenaf composites. The fracture interface between fibre and matrix epoxy is further investigated via scanning electron microscope. Type A kenaf improved up to 199% and 177% as compared to random chopped kenaf for flexural strength and tensile strength, respectively. Scanning electron microscopy analysis shows that resin matrix is properly induced into kenaf fibre gap hence giving additional strength to woven kenaf as compared to random chopped kenaf.